16S rRNA gene sequencing reveals the correlation between the gut microbiota and the susceptibility to pathological scars - Li, Ming; Li, Minghao; Dai, Yingting; Li, Dang; Yu, Han; Liu, Jian; Gao, Hangqi; Zhong, Yi; Huang, Mingquan; Lin, Jing; Xie, Yide; Guo, Zhihui; et al. (Frontiers in Microbiology, 2023)
The gut microbiome profile in patients with pathological scars remains rarely known, especially those patients who are susceptible to pathological scars. Previous studies demonstrated that gut microbial dysbiosis can promote the development of a series of diseases via the interaction between gut microbiota and host. The current study aimed to explore the gut microbiota of patients who are prone to suffer from pathological scars. 35 patients with pathological scars (PS group) and 40 patients with normal scars (NS group) were recruited for collection of fecal samples to sequence the 16S ribosomal RNA (16S rRNA) V3-V4 region of gut microbiota. Though the alpha diversity of gut microbiota showed a significant difference between NS group and PS group, beta diversity indicated that the composition of gut microbiota in NS and PS participants was different, which implied that dysbiosis exhibits in patients who are susceptible to pathological scars. Based on phylum, genus, species levels, we demonstrated that the changing in some gut microbiota (Firmicutes; Bacteroides; Escherichia_coli, etc) may contribute to the occurrence or development of pathological scars. Moreover, the interaction network of gut microbiota in NS and PS group clearly revealed the different interaction model of each group. Our study has preliminary confirmed that dysbiosis exhibits in patients who are susceptible to pathological scars, and provide a new insight regarding the role of the gut microbiome in PS development and progression.